2020
DOI: 10.1093/zoolinnean/zlaa157
|View full text |Cite
|
Sign up to set email alerts
|

The braincase, brain and palaeobiology of the basal sauropodomorph dinosaurThecodontosaurus antiquus

Abstract: Sauropodomorph dinosaurs underwent drastic changes in their anatomy and ecology throughout their evolution. The Late Triassic Thecodontosaurus antiquus occupies a basal position within Sauropodomorpha, being a key taxon for documenting how those morphofunctional transitions occurred. Here, we redescribe the braincase osteology and reconstruct the neuroanatomy of Thecodontosaurus, based on computed tomography data. The braincase of Thecodontosaurus shares the presence of medial basioccipital components of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 91 publications
0
10
0
Order By: Relevance
“…The hearing range of Z. querejazus can be inferred because it is strongly correlated with cochlear duct measurements (derived from extant taxa; Walsh et al, 2009). This equation has already been applied on thalattosuchians (Brusatte et al, 2016), baurusuchids (Dumont et al, 2020), maniraptorans (King et al, 2020) and basal dinosaurs (Ballell et al, 2020). Here, we complete this sampling with the addition of the presently described specimen of Zulmasuchus and other crocodylomorphs from which the data is available but has not been added yet (i.e., P. typus , Pierce et al, 2017; Macrospondylus bollensis and Cricosaurus araucanensis , Herrera et al, 2018; Wilberg et al, 2021; R. aslerensis , Erb & Turner, 2021; “ M .” brachyrhynchus , Schwab et al, 2021; see Figure 12).…”
Section: Discussionmentioning
confidence: 99%
“…The hearing range of Z. querejazus can be inferred because it is strongly correlated with cochlear duct measurements (derived from extant taxa; Walsh et al, 2009). This equation has already been applied on thalattosuchians (Brusatte et al, 2016), baurusuchids (Dumont et al, 2020), maniraptorans (King et al, 2020) and basal dinosaurs (Ballell et al, 2020). Here, we complete this sampling with the addition of the presently described specimen of Zulmasuchus and other crocodylomorphs from which the data is available but has not been added yet (i.e., P. typus , Pierce et al, 2017; Macrospondylus bollensis and Cricosaurus araucanensis , Herrera et al, 2018; Wilberg et al, 2021; R. aslerensis , Erb & Turner, 2021; “ M .” brachyrhynchus , Schwab et al, 2021; see Figure 12).…”
Section: Discussionmentioning
confidence: 99%
“…A ventral ridge on the medulla, as seen in Europasaurus (Figs. 1A, 2C, 3A), seems to be present, although not as pronounced, in Thecodontosaurus 32 , the early-diverging sauropod specimen OUMNH J13596 5 , Spinophorosaurus 31 , Camarasaurus 29 and, potentially, Giraffatitan 6, 21 as well.…”
Section: Discussionmentioning
confidence: 94%
“…Just as potential implications of the floccular recess for VCR/VOR and agility, the morphology of the semicircular canals in respect to agility or lifestyle (e.g. 22,23,24,25,26 ), and the orientation of the lateral semicircular canal in relation to the habitual head posture 27,28,29 , are far from straightforward. If considered as one hint towards a certain orientation of the skull in fossil taxa, the lateral semicircular canal may help to evaluate this issue in concert with aspects such as other osteological correlates and/or ecology (e.g.…”
Section: Supplementary Information and Figuresmentioning
confidence: 99%
“…While the first descriptions considered this taxon as a small quadruped [105], improved knowledge of dinosaur palaeobiology and comparisons with new species led to subsequent reconstruction as a biped [40]. Recent descriptions of the skeletal anatomy of Thecodontosaurus in comparison with other early sauropodomorphs agree with this interpretation [41], and reconstruction of its endocranial anatomy suggests it may have been an agile cursor [47]. We have shown that the appendicular musculature of Thecodontosaurus (figure 8) resembles that of other early branching sauropodomorphs but reveals some derived features that shed light on muscular modifications that occurred during the early evolution of the lineage.…”
Section: Locomotor Function In Thecodontosaurus and The Evolution Of Sauropodomorph Locomotionmentioning
confidence: 99%
“…Numerous fossils of multiple individuals varying in body size and presumed ontogenetic stages are known, many of them showing beautifully preserved muscle scars and other osteological correlates [ 41 ]. The skeletal anatomy of Thecodontosaurus suggests it may have retained a plesiomorphic bipedal and cursorial locomotory mode [ 40 , 41 , 47 ], and preceded the origin of later-diverging members of the clade that acquired larger body sizes [ 22 , 23 ]. These reasons make Thecodontosaurus a valuable source of information about the appendicular muscular anatomy of early sauropodomorphs.…”
Section: Introductionmentioning
confidence: 99%